Transient Ischemic Attack of Hemodynamic Cause - Pigretti, Santiago G.; Zurrú, María C.; Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2015)
Syncope is the abrupt and transient loss of consciousness associated with absence of postural tone, followed by complete and usually rapid spontaneous recovery. In terms of etiology, syncope is classified as reflex (neurally mediated), cardiac, neurologic (vertebrobasilar ischemia) or indeterminate. The neurologic syncope occurs in the setting of stroke or transient ischemic attack, being most frequently associated with focal neurologic symptoms. We report a case of non-neurologic syncope followed with focal neurologic symptoms in a patient with atherosclerosis disease